Reading Yasin, Al Waqiah And Al Mulk At The Ar-Raudlah Al-Qur'aniyyah Karl Mannheim's Perspective - Mubarok, Afriza Syahrul; Saepuloh, Ahmat (Institut Agama Islam Sumatera Barat, 2024)
This study discusses the tradition of reading Surat Yasin, al-Waqiah and al-Mulk after Maghreb prayers at the Ar-Raudlah Al-Qur'aniyyah Islamic Boarding School Sobontoro Tulungagung, as well as exploring the meaning inherent in the tradition of reading these selected letters. This paper uses an ethnographic approach through Living Quran research with qualitative descriptive methods, and uses Karl Maanheim's sociological theory of knowledge. The results of the research with this analysis can be found that the meaning of the tradition of reading Surat Yasin, al-Waqiah and al-Mulk after the Maghreb prayer is: ojective meaning, the students are enthusiastic and respond well to the tradition of reading the three letters. The meaning of expressiveness, the students feel that they get fadhilah from what they have tried, including getting peace of heart and mind, open feeling and cheapness. The meaning of documentary, the perpetrators do not fully know that the traditions they carry out will have a positive impact on them and can be used for a hold in the world until the end of the day. So the routine activity of reading selected letters is very positive for the students to practice for istiqamah and hope for the pleasure of Allah SWT.